Performance Evaluation of DYMO and OLSRv2 Routing Protocols in VANET - Yavuz, UÄŸur; Dael, Fares Abdulhafidh; A. Jabbar, Waheb A. Jabbar Shaif (International Journal of Integrated Engineering, 2020)
Vehicular Ad hoc Networks (VANET) is one of the emerging mobile ad hoc networking paradigms (MANET), where the self-organizing and infrastructure-less nature of this paradigm are a plus and not a limitation. In VANETs, vehicle nodes communicate with each other using wireless links. However, the nodes are highly mobile and the topology of the network changes rapidly. Therefore, the design of routing protocols in VANETs is still a crucial issue. In this paper, we examine two of the most recent routing protocols that proposed for MANETs to select the optimal path between source-destination pairs, namely: Dynamic MANET On-demand (DYMO) and Optimized Link State Routing version 2 (OLSRv2) routing protocols. We evaluated and compared the performance of both protocols based on different parameters under various simulation scenarios